Perception of demonstration of belonging to a certain religion in the context of media representation of terrorism - Narbut, Nickolay P.; Puzanova, Zhanna V.; Larina, Tatiana I. (Journal of the Belarusian State University. Sociology, 2019)
Today media not only reflect modern realities, but also actively form it. It concerns media representation of the topic terrorism, when maximum coverage of audience is reached and psychological consequences of acts of terror increase. The social and psychological processes accompanying the process of media representation, often are transformed to steady stereotypes, in particular an associative array. In this context perception of Islam, which is often identified with Islamism, despite fundamental differences is especially resonant. These data are supported with the results received in 2015 and 2017 during the sociological surveys in the RUDN University. The image of a terrorist received on the basis of the unfinished statements techniques is shown, one of the components of which is a «religiousness», according to data the image is often crossed with perception of Islam. Also the attitude of the Russian and foreign youth to perception of demonstration of belonging to a certain religion (Christianity, Islam, Buddhism, Judaism) in the context of its media representation in media is shown. The main conclusion is that the social stereotypes concerning religious identity are rather strong on stability degree in mass consciousness.